Dinamika Ekonomi Dalam Perspektif Pesantren - Saiful Bakhri; silda Labibi (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2020)
Pesantren as a cultural institution that was born on the initiative and initiative (figure) of the community and is autonomous, since its inception it has been a strategic potential in the middle community life. Although many esantren position themselves (only) as an education and religious institution, but since birth until now several Islamic boarding schools have tried to reposition in addressing various social problems society, such as economic, social and poliyical. Therefore, pesantren are required to make updates that can optimize its potential. In particular, in community empowerment through the economy.